Intron length polymorphism of β-tubulin genes in Colobanthus quitensis across the Argentine Islands-Kyiv Peninsula region - Anastasiia Rabokon; Yuliia Bilonozhko; Anastasiia Postovoitova; Liubov Kalafat; Ivan Parnikoza; Iryna Kozeretska; Igor Andreev; Viktor Kunakh; Yaroslav Pirko; Yaroslav Blume (Український антарктичний журнал)
This work analyses intron length polymorphism of β-tubulin genes in populations of Antarctic pearlwort (Colobanthus quitensis) from the relatively compact region of the Argentine Islands-Kyiv Peninsula (the maritime Antarctic). Analysis of the length polymorphism of the two introns of β-tubulin genes in natural populations of C. quitensis revealed a generally low level of genetic polymorphism. Investigation of the first intron length polymorphism revealed two groups of populations. The population of the largest of Berthelot Islands has representatives of both groups. The second intron length polymorphism of β-tubulin genes identified individual genotypes in 7 of the 11 studied populations of C. quitensis. We speculate that this might be due to the spread of plants from different locations or a combination of changes under different environmental conditions.